Colorectal Resection in Transplant Centers Benefits Kidney But Not Pancreas Transplant Recipients - Weaver, Lauren (Int J Angiol, 2021)
As graft and patient survival rates improve, transplant recipients are likely to undergo colorectal surgery in their lifetime. Current literature on the surgical outcomes of colorectal resection in kidney and pancreas transplant recipients is sparse. This investigation identifies areas of surgical risk for kidney, pancreas, and pancreas–kidney transplant recipients undergoing colorectal resection at transplant and teaching centers. Multivariate logistic regression and linear regression tests computed odds ratios (OR) and coefficients of the linear regression using National Inpatient Sample data from 2005 to 2014 to identify differences in mortality, morbidity, length of stay (LOS), and total hospital charges among people with pancreas transplant alone (PTx), kidney transplant alone (KTx), pancreas and kidney transplant (PKTx), and nontransplant (non-Tx) undergoing colorectal resection in transplant and teaching centers. Of the 2,737,454 individuals who underwent colorectal resection, 138 PTx, 3,874 KTx, 130 PKTx, and 2,733,312 non-Tx met the inclusion criteria. Overall KTx, PTx, and PKTx were not more likely to suffer a mortality. However, PTx were more likely to suffer a mortality in transplant and teaching centers. Overall, PTx and PKTx had significantly higher morbidity odds ratios (PTx OR: 2.268, p  = 0.002; PKTx OR: 2.578, p  < 0.001) along with longer LOS and higher total hospital charges. KTx incurred no increased morbidity risk in transplant centers. Surgeons and transplant recipients should be aware of the increased morbidity and mortality risks when considering colorectal resection at different center types.